Supplementation with sesame oil suppresses genotoxicity, hepatotoxicity and enterotoxicity induced by sodium arsenite in rats (2023)
Background Sesame oil, an edible essential oil, is known to be rich in unsaturated fatty acids, vitamins and lignans with several reported health-promoting benefts. Acute arsenic poisoning produces toxic hepatitis, bone marrow depression and adverse gastrointestinal responses. In this study, we investigated the protective efect of sesame seed oil (SSO) against genotoxicity, hepatotoxicity and colonic toxicity induced by sodium arsenite (SA) in Wistar rats. Methods Twenty-eight male Wistar albino rats were randomly allocated into four groups: control, SA only (2.5 mg/ kg), SA + SSO (4 ml/kg) and SSO alone for eight consecutive days. Liver function and morphology, bone marrow micronuclei induction, colonic histopathology, mucus production and immune expression of Bcl-2, carcinoembryonic antigen (CEA), MUC1 and cytokeratins AE1/AE3 were evaluated. Results SA provoked increased serum activities of liver enzymes, including alanine aminotransferase (ALT) and aspar tate aminotransferase (AST), and caused severely altered morphology of hepatic and colonic tissues with increased frequency of micronucleated polychromatic erythrocytes (MnPCEs/1000PCE) in the bone marrow. In addition, SA triggered increased expression of colonic CEA and MUC1 but weak Bcl-2 immunoexpression. However, cotreatment with SSO demonstrated protective activities against SA-induced damage, as indicated by signifcantly reduced serum ALT and AST, fewer micronucleated bone marrow erythrocytes and well-preserved hepatic and colonic morphologies compared to the SA-treated rats. Furthermore, SSO protected the colonic mucosa by boosting mucus production, elevating anti-apoptotic Bcl-2 expression and reducing CEA expression. GC–MS analysis of SSO revealed that it was predominated by linoleic acid, an omega-3 fatty acid, and tocopherols. Conclusions Our data indicated that SSO protected the liver, colon and bone marrow potentially via anti-infam matory and anti-apoptotic activities. The data suggest that sesame oil has potential therapeutic applications against chemical toxicities induced by arsenic.